Labeling effects of initial juvenile justice system processing decision on youth interpersonal ties - Rowan, Zachary R. (Criminology, 2023)
The juvenile justice system can process youth in myriad ways. Youth who are formally processed, relative to being informally processed, may experience more public and harsh sanctions that label youth more negatively as "deviant." Drawing on labeling theory, the current study evaluates the relative effect of formal justice system processing on the interpersonal dynamics of youth peer networks. Using data from the Crossroads Study, a multisite longitudinal sample of first-time adolescent offenders, the current study applies augmented inverse probability weighting and generalized mixed-effects models to estimate the effects of formal processing on friendship selection processes of homophily and withdrawal and considers whether these effects vary by race and ethnicity. Consistent with expectations of homophily, formally processed youth acquire more new deviant peers and fewer nondeviant peers during the 3 years after their initial processing decision compared with informally processed youth. The findings suggest no differences exist across processing types in withdrawal from friends. These effects were consistent across racial and ethnic groups. Ultimately, this study explores the dynamic interpersonal mechanisms associated with labeling theory and offers additional insight into the negative effects of formal processing.